The glycaemic index : a physiological classification of dietary carbohydrate - Wolever, Thomas M. S. (CABI, 2006)
The glycaemic index (GI) is a measure of the ability of a food to raise blood sugar. This book explores the key issues of the definition of the GI, how to measure the GI of a food, how to apply GI information to meals and diets, the reasons why foods have different GI values, and the impact of altering a diet GI on health and disease